Tanggung Jawab Orang Tua terhadap Anak Angkat dalam Perspektif Hukum Islam - defa iswani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the responsibilities of adoptive parents according to Islamic law. The problem is, many parents still confuse kafalah with tabanni, which is prohibited by religion. As a result, adopted children are often given the name of the adoptive father, considered heirs and treated like mahrams. This violates Surah Al-Ahzab: 5 and triggers inheritance disputes and slander. This normative study examines the limits of adoptive parents' responsibilities in Article 209 of the Compilation of Islamic Law (KHI). In conclusion, the responsibility is limited to providing a living, educating and caring for the child without changing the lineage.